Wellbeing measures for workers: a systematic review and methodological quality appraisal - Jarden, Rebecca J.; Siegert, Richard J.; Koziol-McLain, Jane; Bujalka, Helena; Sandham, Margaret H. (Frontiers in Public Health, 2023)
This systematic review sought to identify the most valid and reliable published measure/s of wellbeing for workers developed between 2010 to 2020. Electronic databases Health and Psychosocial Instruments, APA PsycInfo, and Scopus were searched. Key search terms included variations of [wellbeing OR “well-being”] AND [employee* OR worker* OR staff OR personnel]. Studies and properties of wellbeing measures were then appraised using COnsensus-based Standards for the selection of health Measurement Instruments. Eighteen articles reported development of new wellbeing instruments and eleven undertook a psychometric validation of an existing wellbeing instrument in a specific country, language or context. Generation and pilot testing of items for the 18 newly developed instruments were largely rated ‘Inadequate’; only two were rated as 'Very Good'. None of the studies reported measurement properties of responsiveness, criterion validity, or content validity. The three instruments with the greatest number of positively rated measurement properties were the Personal Growth and Development Scale, The University of Tokyo Occupational Mental Health well-being 24 scale, and the Employee Well-being scale. However, none of these newly developed worker wellbeing instruments met the criteria for adequate instrument design.